Engineering a synthetic RNA segregation system - Hürtgen, Daniel; Mascarenhas, Judita; Vibhute, Mahesh A.; Weise, Laura I.; Mayr, Viktoria S.; Sourjik, Victor; Mutschler, Hannes (Technische Universität Dortmund, 2023)
Cells possess a number of active segregation machineries for both chromosomal and large extrachromosomal DNA elements to avoid stochastic loss during cell division. In contrast, system that can be exploited for active, general segregation of RNA molecules including mRNAs or self-replicating RNA constructs are currently lacking. Here, we present an artificial RNA segregation system derived from the bacterial type II ParMRC plasmid segregation system and the RNA coliphage MS2. We show that fusing the partition protein ParR with the MS2 RNA coat protein enables specific binding to microbeads decorated with RNA-repeats of the archetypical MS2 RNA operator hairpin. Addition of the actin homologue ParM protein triggers efficient and rapid microbeads segregation via ATP-dependent ParM polymerization. Our new RNA partitioning system could be used for specific localization of mRNAs and/or the stable maintenance of self-replicating RNA vectors in various contexts such as living and artificial cells.
ChemSystemsChem; 5(3)
Keywords: MS2; RNA; Protein engineering; Synthetic biology; Segregation; 570; 540